2013
DOI: 10.1021/tx4000123
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Electrophiles Cross-Link Thioredoxins with Redox Relay Partners in Cells

Abstract: Thioredoxin protects cells against oxidative damage by reducing disulfide bonds in improperly oxidized proteins. Previously, we found that the baker's yeast cytosolic thioredoxin Trx2 undergoes cross-linking to form several protein-protein complexes in cells treated with the bifunctional electrophile divinyl sulfone (DVSF). Here, we report that the peroxiredoxin Tsa1 and the thioredoxin reductase Trr1, both of which function in a redox relay network with thioredoxin, become cross-linked in complexes with Trx2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 58 publications
6
44
0
Order By: Relevance
“…21 The preference of alkylation on cysteine and selenocysteine residues in the Trx system by HN2 is also consistent with earlier studies showing that different nitrogen mustards including mechloroethamine and tris(2-chlorethyl)amine, which contain soft electrophilic chloroethyl side chains, predominantly bind to soft nucleophilic sites on proteins including thiolate groups on cysteines and selenolate groups on selenocysteines. 13, 22–25 This is supported by our findings that pretreatment of the Trx system with thiol alkylating agents including iodoacetamide and the half mustard, 2-chloroethyl ethyl sulfide, blocked HN2-induced formation of Trx/TrxR complexes. At the present time, we have no direct evidence on the mechanism mediating the formation of Trx and TrxR cross-links as we were unable to identify intermolecular protein cross-links.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…21 The preference of alkylation on cysteine and selenocysteine residues in the Trx system by HN2 is also consistent with earlier studies showing that different nitrogen mustards including mechloroethamine and tris(2-chlorethyl)amine, which contain soft electrophilic chloroethyl side chains, predominantly bind to soft nucleophilic sites on proteins including thiolate groups on cysteines and selenolate groups on selenocysteines. 13, 22–25 This is supported by our findings that pretreatment of the Trx system with thiol alkylating agents including iodoacetamide and the half mustard, 2-chloroethyl ethyl sulfide, blocked HN2-induced formation of Trx/TrxR complexes. At the present time, we have no direct evidence on the mechanism mediating the formation of Trx and TrxR cross-links as we were unable to identify intermolecular protein cross-links.…”
Section: Discussionmentioning
confidence: 54%
“…31, 32 That Trx formed covalent complexes with TrxR are in agreement with a previous report showing that Trx cross-linked TrxR by structurally unrelated bifunctional electrophiles including HN2 in yeast and human cells; however, these data were based on Western blotting without additional molecular characterization. 25 Our observation that HN2 preferentially cross-linked Trx and TrxR, but not other redox partners, suggests that Trx and TrxR have strong affinities for the HN2 electrophile and are located in close proximity to one another in the cells. Trx is known to have a lower redox potential than protein disulfide isomerase and Trx like protein 1, likely resulting from different p K a’s in their catalytic cysteine residues and distinct amino acids in the vicinity of the redox motifs in these proteins.…”
Section: Discussionmentioning
confidence: 72%
“…23, 29, 42, 43 Our BIAM experiments showed that treatment of oxidized TrxR with HN2 blocks iodoacetamide binding at pH 8.5 in a concentration-dependent manner, confirming that noncatalytic cysteine residues are also targets for HN2 modification. This is supported by our LC-MS/MS analysis that showed that HN2 covalently binds to other cysteine residues in TrxR including cysteine 177, 189, 382, and 383.…”
Section: Discussionmentioning
confidence: 68%
“…This is consistent with earlier studies showing that bifunctional electrophiles agents including HN2 can alkylate thioredoxin and thioredoxin-redox partners, such as peroxiredoxins and TrxR, forming high molecular cross-links in cells. 23 The mechanism mediating the formation of TrxR oligomers is not clear because we have been unable to detect additional HN2 cross-links between dimers and oligomers in the purified enzyme system. This may be due to methodological limitations of our LC-MS/MS analysis because larger peptides in the oligomers may have low ionization efficiency.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation